ANALISIS PENERIMAAN SIMRS DENGAN METODE TECHNOLOGY ACCEPTANCE MODEL DI RSD BALUNG KABUPATEN JEMBER - Intan Winda Rohmatun Imamah; Eri Witcahyo; Sri Utami (Politeknik Negeri Jember, 2022)
SIMRS application is an important component in the application of medical record processing. In Balung Hospital, Jember, the application of SIMRS is still not running optimally, such as entering patient medical record data on SIMRS and the attitude of SIMRS users or admins who forget to enter patient data into SIMRS. This shows the attitude of users who lack awareness in using SIMRS. The purpose of this study was to analyze the acceptance of SIMRS, especially among SIMRS users in Balung Hospital using the Technology Acceptance Model (TAM) approach. The method used is analytic with cross sectional approach with interview and observation techniques. Analysis of research data using univariate analysis and bivariate analysis with simple linear regression. The results of this study show, there was an effect of Perceived Ease of Use on Attitude Toward Using SIMRS, there was an effect of Perceived Ease of Use on Perceived Usefulness, there was no effect of Perceived Usefulness on Attitude Toward Using, there was an effect of Perceived Usefulness on Behavioral Intention to Use SIMRS, there was an effect of Attitude Toward Using SIMRS on Behavioral Intention to Use SIMRS, and there was an effect of Behavioral Intention to Use SIMRS on Actual Usage of SIMRS. The suggestion of this research is that there is a need for regular monitoring and evaluation of the medical record unit and SIMRS in the use of SIMRS based on the performance of the user